Kualitas Good Corporate Governance Dalam Meningkatkan Profitabilitas Bank Syariah Indonesia Periode 2021-2023 - Valentina, Bunga; Yunarsih, Asni; Mustofa, Choirul (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the quality of good corporate governance (GCG) implementation in increasing profitability (ROA) at Bank Sharia Indonesia (BSI) during the 2021-2023 period. This study uses a qualitative descriptive approach to deeply understand how GCG practices and policies are implemented and their contribution to bank profitability. This approach was chosen because it can explore factors influencing GCG implementation and the relationship between GCG policies and BSI financial performance. This study also uses literature studies referring to agency theory and signals to analyze the literature related to GCG and bank financial performance, and to identify inaccuracies in existing research. The results show that the implementation of good GCG principles has a positive effect on increasing return on assets (ROA) at BSI, reflecting operational efficiency and improved risk management, as well as GCG contribution to the profitability of Bank Sharia Indonesia.